Myasthenia gravis associated with anti‐MuSK antibodies developed after SARS‐CoV‐2 infection. (15th September 2021) - Assini, Andrea; Gandoglia, Ilaria; Damato, Valentina; Rikani, Klaudio; Evoli, Amelia; Del Sette, Massimo
Abstract: Introduction: Since the onset of the novel coronavirus pandemic, several neurological complications secondary to SARS‐CoV‐2 infection have been reported, affecting central nervous system, peripheral nervous system and neuromuscular junction. Case report: We present the case of a 77‐year‐old man who developed bulbar myasthenia gravis (MG) eight weeks after SARS‐CoV‐2 infection. The search for serum antibodies against the acetylcholine receptor and the muscle‐specific tyrosine kinase (MuSK), performed by radioimmunoassay (RIA), and the search of low‐density lipoprotein receptor‐related protein 4 antibodies, performed by immunohistochemistry, resulted negative, while anti‐MuSK antibodies were detected by cell‐based assay (CBA). The patient was treated with pyridostigmine (60 mg four times a day) with unsatisfactory clinical response, followed by immunosuppressive therapy (azathioprine 1.5 mg/kg/day) with improvement of MG symptoms after two months of treatment. Discussion: Several viral diseases have been described as associated with the onset of MG, although the underlying mechanisms are not yet fully understood. Similarly, a growing number of scientific reports suggest a correlation between SARS‐CoV‐2 infection and autoimmune diseases. The interest of our case lies in the timing of the MG onset (after 2 months from infection), together with the unusual late onset of anti‐MuSK MG. These elements suggest that coronavirus infection may act as a trigger of the disease. We confirm the importance of CBA in the serological diagnosis of RIA‐negative MG. Abstract : We present the case of myasthenia gravis (MG) developed 8 weeks after SARS‐CoV‐2 infection. The search for serum antibodies against AChR, MuSK (performed by radioimmunoassay), LRP4 (performed by immunohistochemistry), resulted negative, while anti‐MuSK antibodies were detected by cell‐based assay. A growing number of scientific reports suggest a correlation between SARS‐CoV‐2 infection and autoimmune diseases, such as MG. The interest of our case lies in the timing of the MG onset (after two months from infection), together with the unusual late onset of anti‐MuSK MG. These features suggest that coronavirus infection may act as a trigger of the disease.